Creation of new varieties of vegetables and melon crops with good quality and high yield - Rasulov Fakhriddin Fakhmuddinovich; Khakimov Rafik Abdunabievich; Khalimova Mastura Urinbaevna; Islomova Dilfuza Mirakhmatovna; Aripova Shakhnoza Rakhmanovna; Abdaliev Khaitboey; Karimov Bakhtiyor (International Journal on Orange Technologies, 2020)
More than 40 kinds of vegetable and melons are grown in Uzbekistan. From the main vegetable crop varieties tomatoes, cucumbers, onions, carrots, cabbage, beets, sweet and spicy peppers, eggplant, greens, watermelon, melon, pumpkin are planted in large fields. In recent years, export-oriented tours such as rose cabbage, Chinese cabbage, broccoli, kohlrabi, daikon from less common vegetable crops are gaining ground. The soil-climatic conditions of Uzbekistan are rich in vitamins, environmentally friendly, very suitable for the cultivation of export-oriented products. The length of the days of the groom in our country and the high temperature increase the amount of biologically active substances and vitamins contained in the products of vegetables, melons. This is increasing the demand for our products. Today, tomatoes, cucumbers, onions, carrots, cabbage, soup beets, sweet and spicy peppers, eggplant, Redis, greens, cauliflower, broccoli, kohlrabi, iceberg salad, watermelon, melon products are exported from vegetable crops. From Uzbekistan in January-July, 2020 amounted to 147.1 million of US dollars, vegetables were exported. In order to increase the export potential, more than 60 varieties of vegetables and melons have been created at the Research Institute of vegetable, melons and potatoes in recent years. The main style of our selection works is separated from the collection the forms of motherhood and chattering works are conducted. Descendants of hybrids are divided on the basis of tests, prospective forms are selected. Perspective lines are divided into perspectives for a test the new variety in standard variety. Then, small and large varieties are tested with zoned varieties in Test nurseries. At the same time, primary seeding of perspective lines is organized. Prospects based on the results of the competition and production will be submitted to the state variety test Commission. On the basis of this method, a selection of tomato, cucumber, onion, watermelon and melon crops is carried out. This article describes the results of the selection work obtained in recent years.